Hollow Fiber Hemodialysis Imprinted Membrane Based on Eugenol for Human Blood Filter - Djunaidi, Muhammad Cholid; Maharani, Nesti Dwi; Pardoyo, Pardoyo; Raharjo, Yanuardi (Universitas Gadjah Mada, 2024)
Kidney failure is a kidney function disorder that occurs in more than 90.00% of people in the world, especially in developing countries. In 2013, around 12.50% of the 25 million population experienced kidney failure and 78.00% had to undergo dialysis for life. In this research, a hemodialysis method was developed, namely molecularly imprinted membrane (MIM), which has high selectivity for urea molecules with high binding capacity using a membrane in the form of hollow fiber. Variations in research use urea transport concentrations such as 50, 200, and 300 ppm. The analysis using UV-vis spectrophotometry on HFHIM with a solution mixture of 50 ppm showed that the receiving phase by the membrane was 70.48% urea, 12.97% creatinine, and 9.42% vitamin B12. Meanwhile, the feed phase is 28.25% urea, 85.41% creatinine and 88.64% vitamin B12. When using HFHNIM, the receiving phase is urea 44.78%, creatinine 58.51%, and vitamin B12 31.00%. Meanwhile, the feed phase is 54.55% urea, 40.57% creatinine, 68.29% vitamin B12. The selectivity of HFHIM for urea is better than creatinine and vitamin B12 compared to HFHNIM, in the order of selectivity urea > creatinine > vitamin B12.